La atención al cliente y su incidencia en las ventas de la panificadora El Relámpago Ipsanfer Cía. Ltda del Canton La Mana. - Añarumba Lozano, Karolyn Mishell (2022)
The purpose of this research is to present an analysis of customer service and its impact on the sales of the El Relámpago bakery in the La Maná canton, through which the problem of the level of customer satisfaction, their relationship with sales and customer loyalty. In this way it was possible to carry out an exhaustive investigation on the performance of the collaborators and to know the cause that urges the clients to satisfy their needs, either for their attention, for the quality of the products or the infrastructure of the establishment, due to which is a fundamental point for the investigation, the theoretical framework composed of the concepts on: customer service and sales, having a qualitative and quantitative research modality, in the investigation the theoretical method was applied: historical logical, deductive, synthetic analytical and the empirical method: evaluation by experts, in addition the descriptive and corrective investigation was improved. The methodology includes a bibliographical research work, instruments such as the survey and the interview were also applied, which were carried out and applied, obtaining results expressed in percentages, statistical tables and graphs, ending with this analysis of results, revealing the initial problem. Being in this way that the majority of the clients affirm to have obtained an excellent service in obtaining the product by means of which the cause of the incidence that the attention to the client has in the sales was obtained.